The Biblical world. - Harper, William Rainey, 1856-1906; Burton, Ernest DeWitt, 1856-1925; Mathews, Shailer, 1863-1941 (Chicago, University of Chicago Press., 1916)
"Books for New Testament study ... [By] Clyde Weber Votaw" v. 26, p. 271-320; v. 37, p. 289-352.
"Books for Old Testament study. [By] John Merlin Powls Smith" v. 30, p. 135-160, 302-320, 383-400.
Vols. 11-14 include "Theological and Semitic literature; a bibliographical supplement to the American journal of theology, the American journal of Semitic languages and literatures, and the Biblical world. By W. Muss-Arnolt," 1898-99.
"A journal of the awakening church."
Editors: 1893-1905, W.R. Harper.--1906-12, E.D. Burton.--1913-20, S. Mathews.
Also issued online.
Vols. 1-27, 1893-1906, in v. 28.
Merged with: American journal of theology, ISSN 1550-3283, to form: The journal of religion, ISSN 0022-4189.
PREMARC/SERLOC merged record
Keywords: Bible -- Criticism, interpretation, etc. -- Periodicals; Bible -- Study and teaching -- Periodicals; Bible; Study skills; Periodicals -- U.S.A. -- 1893-1920.; Criticism, interpretation, etc; Periodicals